Grid Computing Approach for Dynamic Load Balancing - Morey, Kapil B; Sachin B, Jadhav (International Journal of Computer Sciences and Engineering, 2025)
Grid computing technology can be seen as a positive alternative for implementing high-performance distributed computing. The goal of Grid computing is to create the illusion of virtual computer out of a large collection of connected heterogeneous nodes sharing various resources. The Grid system needs competent load balancing algorithms for the distribution of tasks in order to increase performance and efficiency. The process of identifying requirements, matching resources to applications, allocating those resources, and scheduling and monitoring grid resources over time in order to run grid applications efficiently is known as Grid Resource Management. The first phase of resource management is resource discovery. The next step is monitoring and scheduling. Monitoring keeps the details of the resources and scheduling guides the job to appropriate resource. The resources which are heavily loaded act as server of task and the resources which are lightly loaded act as receiver of task. Task relocation takes place from the node which has high load towards the node which has fewer loads. The main aim of load balancing is to provide a distributed, low cost scheme that balances the load across all the processors. In this paper a dynamic load balancing algorithm is proposed in a simulated grid environment which fulfils the objective to achieve high performance computing by optimal usage of geographically distributed and heterogeneous resources in the grid environment.